2009
DOI: 10.1007/s11568-010-9134-1
|View full text |Cite
|
Sign up to set email alerts
|

Genetic determinants of immune-response to a polysaccharide vaccine for typhoid

Abstract: Differences in immunological response among vaccine recipients are determined both by their genetic differences and environmental factors. Knowledge of genetic determinants of immunological response to a vaccine can be used to design a vaccine that circumvents immunogenetic restrictions. The currently available vaccine for typhoid is a pure polysaccharide vaccine, immune response to which is T-cell independent. Little is known about whether genetic variation among vaccinees associates with variation in their a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 49 publications
0
15
0
Order By: Relevance
“…Individuals (n ¼ 1000), unrelated at least to the first-cousin level based on family history report, aged 14 years or older, inhabiting a socio-economically depressed locality of Kolkata (formerly, Calcutta), India, were recruited using a statistical sampling design, 34 with institutional ethical approval and written individual informed consent. Exclusions included: (a) pregnant and lactating women and (b) based on self-report, individuals who had ever been diagnosed with cholera or had suffered from diarrhea or vomiting during the week preceding recruitment.…”
Section: Study Participantsmentioning
confidence: 99%
See 1 more Smart Citation
“…Individuals (n ¼ 1000), unrelated at least to the first-cousin level based on family history report, aged 14 years or older, inhabiting a socio-economically depressed locality of Kolkata (formerly, Calcutta), India, were recruited using a statistical sampling design, 34 with institutional ethical approval and written individual informed consent. Exclusions included: (a) pregnant and lactating women and (b) based on self-report, individuals who had ever been diagnosed with cholera or had suffered from diarrhea or vomiting during the week preceding recruitment.…”
Section: Study Participantsmentioning
confidence: 99%
“…33 Insights into the impact of genetic variation in vaccinees on AR has been obtained for some vaccines. 24,34,35 In this study, we have investigated, for the first time, whether variation in the genomic backgrounds of vaccinees contributed to variation in immunological response to the killed whole-cell bivalent oral cholera vaccine, which has been introduced in India in 2010.…”
Section: Introductionmentioning
confidence: 99%
“…This variation in immune response is due to differences at the genetic level along with environmental factors. Studies regarding genetic factors responsible for the immunological response to a vaccine may be helpful to develop a vaccine that can overcome immunogenetic restrictions [8]. Studies in endemic areas have reported that around 19-58% of patients are often exposed to S. Typhi and other related infections and therefore develop protective levels of anti-Vi antibodies in the serum prior to vaccination [22,83,84].…”
Section: Current Prophylaxis and Treatmentmentioning
confidence: 99%
“…Studies in endemic areas have reported that around 19-58% of patients are often exposed to S. Typhi and other related infections and therefore develop protective levels of anti-Vi antibodies in the serum prior to vaccination [22,83,84]. Such observation suggest that the vaccines can induce a strong post vaccination antibody levels in individuals with/without pre-vaccination antibody levels against S. Typhi [8].…”
Section: Current Prophylaxis and Treatmentmentioning
confidence: 99%
See 1 more Smart Citation